Pengaruh Organizational Citizenship Behavior terhadap Kinerja Karyawan melalui Komitmen Organisasi sebagai Variabel Mediasi pada TelkoMedika Jatim Bali - Berlian Putri Aliefah; Muhammad Husain (Universitas Negeri Surabaya, 2026)
This study aims to analyze the effect of organizational citizenship behaviour on employee performance through organizational commitment. This study used a quantitative approach. The sample for this study consisted of 50 employees of Company X. The sample was selected using saturated sampling. This study used SEM-PLS data analysis supported by SmartPLS 3.2.9 software. The results of this study indicate that organizational citizenship behaviour has a significant and positive effect on employee performance. Furthermore, organizational citizenship behaviour also has a significant and positive effect on organizational commitment. Organizational commitment has a significant and positive effect on employee performance. Furthermore, it was found that organizational citizenship behaviour has a significant positive effect on employee performance through organizational commitment as a mediating variable. Thus, organizational citizenship behaviour not only directly impacts performance but also indirectly through increased employee organizational commitment. The implications of this study indicate that companies need to strengthen organizational citizenship behaviour and organisational commitment by fostering supportive work environments, developing employees, and implementing appropriate reward systems to improve employee performance.